Hydrogels: Inwards Interweaving of Polymeric Layers within Hydrogels: Assembly of Spherical Multi‐Shells with Discrete Porosity Differences (Adv. Funct. Mater. 41/2013). (4th November 2013) - Pan, Houwen Matthew; Beyer, Sebastian; Zhu, Qingdi; Trau, Dieter
<x xml:space="preserve">Abstract</x> Multiple shells with discrete porosities are created by D. Trau and co‐workers on page 5108, within the matrix of a hydrogel. The front cover image illustrates, from both 2D and 3D perspectives, the increasing density of concentric shells from inner‐ to outermost layer. The 2D confocal images reflect the unique inwards interweaving behavior of polyallylamine (red) and polystyrenesulfonic acid (green) to produce a yellow layer. Intricate multi‐porous architectures can be fabricated via this facile and easily tunable approach. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>